Clinical Features and Treatment Response to Topical Steroids in Ethnic and Racial Minority Patients With Eosinophilic Esophagitis - Ocampo, Adolfo A.; Xue, Zeyun; Chang, Nicole C.; Thakkar, Kisan P.; Reddy, Sumana B.; Greenberg, Sydney B.; Lee, Christopher J.; Ketchem, Corey J.; Redd, Walker D.; Eluri, Swathi; Reed, Craig C.; Dellon, Evan S. (The American journal of gastroenterology, 2024)
INTRODUCTION:Differences in eosinophilic esophagitis (EoE) presentation and outcomes by ethnicity or race remain understudied. We aimed to determine whether EoE patients of Hispanic/Latinx ethnicity or non-White race have differences in presentation at diagnosis or response to topical corticosteroid (tCS) treatment.METHODS:This retrospective cohort study included subjects of any age with a new diagnosis of EoE and documentation of ethnicity or race. For those who had treatment with tCS and follow-up endoscopy/biopsy, we assessed histologic response (<15 eosinophils/hpf), global symptom response, and endoscopic response. Hispanic EoE patients were compared with non-Hispanics at baseline and before and after treatment. The same analyses were repeated for White vs non-Whites.RESULTS:Of 1,026 EoE patients with ethnicity data, just 23 (2%) were Hispanic. Most clinical features at presentation were similar to non-Hispanic EoE patients but histologic response to tCS was numerically lower (38% vs 57%). Non-White EoE patients (13%) were younger at diagnosis and had less insurance, lower zip code-level income, shorter symptom duration, more vomiting, less dysphagia and food impaction, fewer typical endoscopic features, and less dilation. Of 475 patients with race data treated with tCS, non-Whites had a significantly lower histologic response rate (41% vs 59%; P = 0.01), and odds of histologic response remained lower after controlling for potential confounders (adjusted odds ratio 0.40, 95% confidence intervals: 0.19-0.87).DISCUSSION:Few EoE patients at our center were Hispanic, and they had similar clinical presentations as non-Hispanics. The non-White EoE group was larger, and presentation was less dysphagia-specific. Non-White patients were also less than half as likely to respond to tCS.